PENELUSURAN PEMINATAN JURUSAN DI PERGURUAN TINGGI PADA SMA NEGERI 7 MEDAN - Dhita Adriani Rangkuti; Rosmita Sari Siregar; Sufika Sary; Wirda Lilia; Yovie Ernanda (Institut Informatika dan Bisnis Darmajaya, 2019)
At present there are many students who are less interested in continuing to a higher level while these students have high achievements. According to the Minister of Education (2011),